Carbohydrate Sources, Within a Higher Protein Breakfast, Differentially Effect Postprandial Appetite Response in Adults with Metabolic Syndrome: A Pilot Study. (29th May 2020) - Walker, Sam; Baum, Jamie; Hawley, Aubree; Tacinelli, Angela; Enderlin, Drake; Fellinger, Mckenzie
Abstract: Objectives: The objective of this study was to determine the effect of carbohydrate source within a higher protein breakfast on postprandial appetite response in adults with metabolic syndrome. Methods: Fourteen adults with metabolic syndrome were randomly assigned to consume one of three iso-caloric, higher protein breakfasts (352 kcal; 26.5 ± 0.3 g Pro; 20.0 ± 0.5 g CHO; 19.8 ± 0.3 g 18.0 ± 0.1 g Fat) containing servings of different carbohydrate sources: white potatoes ( n  = 5; 5 female; 37.6 ± 8.5 y; 98.0 ± 14.1 kg; 39.5 ± 7.3 BMI); 2) processed potatoes (hash browns) ( n  = 2; 1 female, 1 male; 53.0 ± 15.0 y; 81.4 ± 17.0 kg; 29.6 ± 3.0 BMI); or 3) starchy carbohydrate (white rice; n  = 5; 4 female, 1 male; 33.6 ± 5.0 y; 95.1 ± 18.2 kg; 35.3 ± 4.7 BMI). All participants reported to the lab following an overnight fast. Participants were served their assigned meal (quiche) and were given 15 minutes to fully consume the entire portion. Appetite was assessed via visual analogue scale (VAS) with opposing anchors (e.g., "extremely hungry" or "not hungry at all") at time points 0, 15, 30, 60, 90, 120, 180 and 240 min. Data were analyzed using Prism GraphPad version 8.0. Significance was set at P  < 0.05. Results: Although not significant, participants who consumed the starchy carbohydrate meal reported increased hunger (182%), desire to eat (64%), and decreased fullness (8%) when compared to participants consuming the potato meal. In addition, the starchy carbohydrate meal consumption was a significantly associated with a desire for sweetness ( P  < 0.05). No significant differences in appetite were observed between participants consuming the potato meal and the processed potato meal. Conclusions: Preliminary results indicate the source of carbohydrate as part of a higher protein breakfast influences postprandial appetite response in adults with metabolic syndrome, however further research is needed. Funding Sources: Alliance for Potato Research and Education.